Dottie - Coplans, Peta (Boston : Houghton Mifflin, 1994)
Dottie the dog persists in her love of gardening, even though her parents think it is improper behavior for a canine.
"Originally published in Great Britain in 1993 by Andersen Press Ltd."--facing t.p.